Keterbatasan Sarana dan Prasarana yang Mengakibatkan Penghambatan dalam Upaya Pembinaan di Lembaga Pemasyarakatan Kelas IIA Banceuy - Muhammad Saleh Armand Pratama; Dey Ravena (Bandung Conference Series: Law Studies, 2024)
Abstract. This research focuses on what factors are the limitations of facilities and infrastructure and what impacts arise from the limitations of facilities and infrastructure which result in obstacles in coaching efforts at the Class IIA Banceuy Correctional Institution. This research uses a qualitative approach with descriptive analysis. This qualitative approach is used to understand how conditions and situations occur. The data collected is in the form of a description of the actual (naturalistic) situation in the field in the form of a detailed description that explains something as it is and provides a clear picture of the limitations of facilities and infrastructure that result in obstacles to development efforts. After observing the Class IIA Banceuy Penitentiary, there were limited facilities and infrastructure due to a large fire that occurred on Saturday 23 April 2016 which caused the facilities in the prison to burn up to 90%. This incident occurred due to a number of inmates going on a rampage due to a misunderstanding between prison officers. and the inmates, therefore efforts to develop goals are hampered. The limited facilities and infrastructure at the Class IIA Banceuy Prison have an impact on the physical and mental condition of the inmates. This limited facility and infrastructure also triggers the mental condition of the prisoners to become unfavorable. Limitations in prayer rooms, library rooms, visiting rooms, education rooms and inadequate skills can make prisoners feel stressed and even depressed due to lack of social interaction and social activities. Abstrak. Penelitian ini berfokus kepada faktor apa yang menjadi Keterbatasan Sarana dan Prasarana dan dampak apa yang timbul dari adanya Keterbatasan Sarana dan Prasarana yang mengakibatkan penghambatan dalam upaya pembinaan di Lembaga Pemasyarakatan Kelas IIA Banceuy. Penelitian ini menggunakan pendekatan Kualitatif dengan analisis Deskriptif. Pendekatan Kualitatif ini digunakan untuk memahami bagaimana kondisi dan situasi yang terjadi. Data yang di kumpulkan berupa gambaran keadaan yang senarnya (naturalistik) di lapangan berupa uraian detail yang menjelaskan sesuatu apa adanya serta memberi gambaran yang jelas mengenai Keterbatasan Sarana Dan Prasarana Yang Mengakitbatkan Penghambatan Dalam Upaya Pembinaan. setelah dilakukan observasi ke Lembaga Pemasyarakatan Kelas IIA Banceuy adanya Keterbatasan Sarana dan Prasarana diakibatkan adanya kebakaran besar yang terjadi pada Sabtu 23 April 2016 yang menyebabkan terbakarnya fasilitas dalam Lapas hingga 90% kejadian ini terjadi akibat adanya sejumlah narapidana yang mengamuk akibat adanya kesalah pahaman antara petugas lapas dan para narapidana maka dari itu terhambatnya upaya tujuan pembinaan Keterbatasan sarana dan prasarana di Lapas Kelas IIA Banceuy berdampak pada kondisi fisik dan mental narapidana. Keterbatasan Sarana dan Prasarana ini juga menjadi pemicu kondisi mental para narapidana menjadi tidak baik. Keterbatasan pada ruang ibadah, ruang perpustakaan, ruang kunjungan, ruang pendidikan maupun keterampilan yang tidak memadai dapat membuat narapidana merasa stress hingga depresi karena kurangnya interaksi sosial dan kegiatan sosial.